Computationally Guided Design of Single-Chain Variable Fragment Improves Specificity of Chimeric Antigen Receptors - Andrey Krokhotin; Hongwei Du; Koichi Hirabayashi; Konstantin Popov; Tomohiro Kurokawa; Xinhui Wan; Soldano Ferrone; Gianpietro Dotti; Nikolay V. Dokholyan (Molecular Therapy: Oncolytics, 2019)
Chimeric antigen receptor (CAR)-T cell-based immunotherapy of malignant disease relies on the specificity and association constant of single-chain variable fragments (scFvs). The latter are synthesized from parent antibodies by fusing their light (VL) and heavy (VH)-chain variable domains into a single chain using a flexible linker peptide. The fusion of VL and VH domains can distort their relative orientation, thereby compromising specificity and association constant of scFv, and reducing the lytic efficacy of CAR-T cells. Here, we circumvent the complications of domains’ fusion by designing scFv mutants that stabilize interaction between scFv and its target, thereby rescuing scFv efficacy. We employ an iterative approach, based on structural modeling and mutagenesis driven by computational protein design. To demonstrate the power of this approach, we use the scFv derived from an antibody specific to a human leukocyte antigen A2 (HLA-A2)-HER2-derived peptide complex. Whereas the parental antibody is highly specific to its target, the scFv showed reduced specificity. Using our approach, we design mutations into scFvs that restore specificity of the original antibody. Keywords: protein design, single-chain variable fragment, chimeric antigen receptor, CAR T, antibody, cancer, HER2, HLA-A2, MHC, immunotherapy